Peningkatan kompetensi guru dalam penyusunan rencana pelaksanaan pembelajaran (RPP) Kurikulum 2013 melalui pendampingan di MIN 1 Aceh Barat Daya - Mirdas, Tasyfin (Jurnal Pendidikan dan Pengabdian Vokasi (JP2V), 2020)
This research is to find out the improvement of teacher competency in preparing the 2013 Curriculum Learning Implementation Plan (RPP) through mentoring in MIN 1 Southwest Aceh 2018/2019 Academic Year. The subject of this school action research is Teachers MIN 1 Southwest Aceh. The number of teachers is 8 with a total of 1 male and 7 female. This School Action Research was conducted in Sep-tember to November of the 2018/2019 academic year Odd semester. The methodology of this study is the School Action Research (PTS) consisting of two cycles and each cycle consists of one meeting. In each cycle consists of planning, implementation, observation and reflection. The research procedure consisted of pre-research, planning cycle one, implementing cycle one, observing cycle one, reflection cycle one, planning cycle two, implementing cycle action two, observing cycle two and reflection cycle two. Data collection techniques in this study were interviews, observation, and discussion. Observation data was carried out by filling out the teacher motivation questionnaire and guidelines for evaluating the 2013 curriculum RPP. Through mentoring, it could improve the motivation and competence of teachers in preparing the 2013 Curriculum RPP completely in MIN 1 Southwest Aceh 2018/2019 Academic Year. This can be proven from the results of observations / observations which show that an increase in teach-er competence in preparing the 2013 Curriculum RPP from cycle to cycle. In the first cycle the average value of the 2013 curriculum curriculum RPP components was 69% and in the second cycle 83%. So, there was a 14% increase from cycle I.